Kualitas Isi dan Kalimat Langsung pada Novel Perfect Couple Karya Asri Aci sebagai Sumber Bacaan Siswa SMA Kelas XII - Dela Agustin Erikasari; Alliya Setiawan Putri; Nurul Hikmah; Narista Amellea Dinata; Najwa Sakinah; Asep Purwo Yudi Utomo; Molas Warsi Nugraheni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Currently, many novels can be read and are available on various social media platforms. These novels are expected to achieve the existing learning objectives and enable students to understand and implement the results of their learning activities well. The purpose of this study is to analyze the quality of content and direct sentences in the novel to determine whether or not the novel Perfect Couple is suitable as a reading resource for high school students in grade XII. This research will analyze various aspects of the quality of content and direct sentences, such as the level of content with the subject matter, the level of suitability of direct sentences with the level of students' reading ability, and others. The descriptive-qualitative method is used in this study by describing and analyzing the quality of content and direct sentences in the text of the novel Perfect Couple by Asri Aci. So, the researcher finds descriptive data and then looks for findings to be explained in detail. The descriptive method in this study is used to determine the quality of content and direct sentences in the novel Perfect Couple by Asri Aci. The data collected is in the form of words and pictures, not numbers. From the analysis that has been done, there are several quotations from the quality of content and direct sentences in the novel Perfect Couple by Asri Aci. The analysis results in this article are expected to add deeper understanding and knowledge about the quality of content and direct sentences contained in the novel. The first result of this research is that ten positive content qualities provide benefits to readers so that they can be used as reading material for high school students in class XII. The second result of this research is that there are 2,562 direct sentences consisting of 1,401 news sentences, 964 question sentences, and 199 command sentences.